Solvent-Driven Chirality Switching of a Pillar[4]arene[1]quinone Having a Chiral Amine-Substituted Quinone Subunit - Liu, Chunhong; Yu, Zhipeng; Yao, Jiabin; Ji, Jiecheng; Zhao, Ting; Wu, Wanhua; Yang, Cheng (Frontiers in Chemistry, 2021)
Several new chiral pillar[4]arene[1]quinone derivatives were synthesized by reacting pillar[4]arene[1]quinone (EtP4Q1), containing four 1,4-diethoxybenzene units and one benzoquinone unit, with various chiral amines via Michael addition. Due to the direct introduction of chiral substituents on the rim of pillar[n]arene and the close location of the chiral center to the rim of EtP4Q1, the newly prepared compounds showed unique chiroptical properties without complicated chiral resolution processes, and unprecedented high anisotropy factor of up to −0.018 at the charge transfer absorption band was observed. Intriguingly, the benzene sidearm attached pillar[4]arene[1]quinone derivative 1a showed solvent- and complexation-driven chirality inversion. This work provides a promising potential for absolute asymmetric synthesis of pillararene-based derivatives.